Evaluasi Kinerja Layanan Angkutan Umum Pengguna Program OK-OTrip - Sinai Handayani; Irani Handalia (Institut Transportasi dan Logistik Trisakti, 2021)
The OK-OTrip program is an integrated public transportation system program launched by the DKI Jakarta Provincial Government that applies low fares with the aim of attracting people to use public transportation more in travel activities. This study aims to see whether the performance of the program is good enough or not, so that in the future steps and policies can be taken that can improve the performance of the program. Public transport service performance subject for the evaluation is from output part, performance assessment conducted toward users instead of operator side. Data is obtained via static & dynamic surveys as well as interviews with Route OK-3 passengers during observation days. Refer to Directorate General of Land Transportation service standard, the analysis result shows service performance of public transport in OK-OTrip Program for South Jakarta region OK-3 Route is quite satisfactory. %. Based on public perceptions of the waiting time, travel time, value of fare, convenience, driver behavior, comfort, safety and cleanliness of the Route OK-3 fleet, it concluded that the quality of public transport services OK-3 Route is very good.The main reason for using OK-3 is due to cheap tariff. According to the research result of OK-OTrip program intention and purpose re conversion of the society favour to use mass-public transport, it is deems successfull as results shown that 83% of respondends owned private vehicle.